Oil absorption sponge as well as preparation method and application thereof

By combining three-dimensional porous polymer matrix with thermosetting resin, the problems of poor selectivity and poor recycling performance of existing oil absorbing materials are solved, and efficient oil adsorption and recycling are achieved, reducing waste solid generation and use costs .

CN119161630APending Publication Date: 2024-12-20CHINA PETROLEUM & CHEMICAL CORP +2
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202310728450.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-19
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The existing oil-absorbing materials have poor selectivity and poor recycling performance, resulting in low adsorption of oil and inability to desorption, resulting in waste of resources and environmental pollution.

Method used

The oil-absorbing sponge combined with a three-dimensional porous polymer matrix and a thermosetting resin is used to cure under vacuum to maintain high resilience and porosity, achieve superhydrophobic and super-lipophilic properties, and enhance the adsorption capacity and recycle of oil products.

Benefits of technology

The selectivity and adsorption capacity of the oil product are significantly improved. After 30 cycles, the adsorption capacity is basically without attenuation, reducing the cost of waste solid generation and use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119161630A_ABST
    Figure CN119161630A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of high polymer material modification, in particular to oil absorption sponge and a preparation method and application thereof. The oil absorption sponge comprises a three-dimensional porous polymer matrix and thermosetting resin coated on the three-dimensional porous polymer matrix, the oil adsorption capacity of the oil adsorption sponge is not less than 30 g / g; the saturated adsorption capacity of the oil-absorbing sponge on oil products is still not less than 30g / g after the oil-absorbing sponge is recycled for 30 times of adsorption-desorption. The oil-absorbing sponge disclosed by the invention has super-hydrophobic and super-oleophylic properties on the basis of keeping the original high resilience and high porosity of the three-dimensional porous polymer matrix, is used for treating oily sewage, has strong selectivity on oil products in the oily sewage, has large adsorption capacity on the oil products, can be recycled, and can be used for treating the oily sewage. And the adsorption capacity is basically not attenuated under the condition of 30 times of recycling.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer material modification, and in particular to an oil-absorbing sponge and a preparation method and application thereof. Background Art

[0002] Oil leakage is inevitable in the petrochemical production process. For example, during the sampling process and the shutdown and maintenance of the equipment, oily wastewater is often produced. At present, there are two ways to deal with this phenomenon. The first is to directly discharge it into the oily wastewater pool and accumulate it for a period of time before separating the oil and water. This treatment method is suitable for the treatment of a large amount of expected oily wastewater; the other method is to use activated carbon, oil-absorbing felt and other adsorption methods on site for adsorption, and try it for small-scale and non-fixed-point waste oil treatment. However, due to the low adsorption capacity of activated carbon, oil-absorbing felt, etc., and the poor selective adsorption capacity for oil, the amount used is very large, and desorption cannot be carried out after adsorption is completed, and subsequent incineration or landfill treatment is carried out, resulting in waste of resources and secondary environmental pollution.

[0003] Therefore, it is urgent to develop a high-performance oil-absorbing sponge with good selectivity and a large number of recycling times. Summary of the invention

[0004] The purpose of the present invention is to overcome the difficulties of poor selectivity of oil absorption materials and poor recycling performance in the prior art, and to provide an oil absorption sponge and a preparation method and application thereof. The oil absorption sponge has good resilience and strong adsorption capacity for oil products; the oil absorption sponge is used for oily wastewater treatment, has strong selectivity for oil products in oily wastewater, has a large adsorption capacity for oil products and can be recycled.

[0005] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides an oil-absorbing sponge, which includes a three-dimensional porous polymer matrix and a thermosetting resin coated on the three-dimensional porous polymer matrix; the saturated adsorption capacity of the oil-absorbing sponge for oil is not less than 30g / g; the saturated adsorption capacity of the oil-absorbing sponge for oil is still not less than 30g / g after 30 adsorption-desorption cycles.

[0006] A second aspect of the present invention provides a method for preparing the oil-absorbing sponge of the present invention, the method comprising:

[0007] The oil-absorbing sponge is obtained by dispersing a solution containing a thermosetting resin prepolymer and a curing agent into a three-dimensional porous polymer matrix and curing the matrix under vacuum conditions.

[0008] The third aspect of the present invention provides an application of the oil-absorbing sponge of the present invention in treating oily wastewater.

[0009] Through the above technical scheme, the oil-absorbing sponge of the present invention has super-hydrophobic and super-oleophilic properties on the basis of maintaining the high resilience and high porosity of the original three-dimensional porous polymer matrix. The oil-absorbing sponge has good resilience and strong adsorption capacity for oil products. The oil-absorbing sponge is used for oily wastewater treatment, has strong selectivity for oil products in oily wastewater, has a large adsorption capacity for oil products and can be recycled. The adsorption capacity is basically not attenuated after being recycled for 30 times. Compared with traditional activated carbon, oil-absorbing felt and other materials, the generation of waste solids is significantly reduced, and the cost of use is reduced at the same time.

[0010] The preparation method described in the present invention disperses (for example, extrusion absorption dispersion, spray absorption dispersion) a solution containing a thermosetting resin prepolymer and a curing agent into a three-dimensional porous polymer matrix and then heats and cures it in a vacuum. The thermosetting resin can be cured on the three-dimensional porous polymer matrix while maintaining the high resilience and high porosity of the original three-dimensional porous polymer matrix, so that the adsorption capacity of the oil-absorbing sponge described in the present application is basically not attenuated when it is recycled 30 times. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 is a scanning electron microscope (SEM) image of the oil-absorbing sponge prepared in Example 1;

[0012] Figure 2 is a scanning electron microscope (SEM) image of the oil-absorbing sponge prepared in Example 1 after 30 cycles;

[0013] Figure 3 is a scanning electron microscope (SEM) image of the porous melamine-formaldehyde sponge matrix of Example 1;

[0014] Figure 4 is a scanning electron microscope (SEM) image of the oil-absorbing sponge prepared in Comparative Example 1;

[0015] Figure 5 This is a scanning electron microscope (SEM) image of the oil-absorbing sponge prepared in Comparative Example 1 after 30 cycles. DETAILED DESCRIPTION

[0016] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0017] The first aspect of the present invention provides an oil-absorbing sponge, which includes a three-dimensional porous polymer matrix and a thermosetting resin coated on the three-dimensional porous polymer matrix; the saturated adsorption capacity of the oil-absorbing sponge for oil products is not less than 30g / g; the saturated adsorption capacity of the oil-absorbing sponge for oil products is still not less than 30g / g after 30 cycles of adsorption-desorption. The oil-absorbing sponge of the present invention has super-hydrophobic and super-oleophilic properties on the basis of maintaining the high resilience and high porosity of the original three-dimensional porous polymer matrix, and the oil-absorbing sponge has good resilience and strong adsorption capacity for oil products.

[0018] According to a preferred embodiment of the present invention, the mass of the thermosetting resin accounts for 0.5-5%, preferably 2-3%, of the total mass of the sponge.

[0019] According to a preferred embodiment of the present invention, the saturated adsorption capacity of the oil-absorbing sponge for oil is 30-50 g / g.

[0020] The oil-absorbing sponge of the present invention has strong selectivity for oil products in oily wastewater, large adsorption capacity for oil products and can be recycled. The adsorption capacity is basically not attenuated after being recycled for 30 times. According to a preferred embodiment of the present invention, the saturated adsorption capacity of the oil-absorbing sponge for oil products is still 30-50g / g after 30 desorption-adsorption cycles.

[0021] In the present invention, the thermosetting resin can be selected from a wide range, and conventional thermosetting resins in the field can meet the requirements of the present invention. According to a preferred embodiment of the present invention, the thermosetting resin is selected from at least one of phenolic resin, epoxy resin, urea-formaldehyde resin, unsaturated polyester resin and silicone resin; preferably selected from at least one of phenolic resin, epoxy resin and silicone resin.

[0022] In the present invention, the three-dimensional porous polymer matrix only needs to have a through-hole structure inside and a porosity greater than 70%. According to a preferred embodiment of the present invention, the three-dimensional porous polymer matrix is ​​selected from at least one of melamine-formaldehyde sponge, polyurethane sponge and ethylene-vinyl acetate sponge, preferably melamine-formaldehyde sponge.

[0023] In the present invention, the pore size of the oil absorbing sponge can be selected in a wide range. According to a preferred embodiment of the present invention, the pore size of the oil absorbing sponge is 10-500 μm, preferably 100-400 μm.

[0024] In the present invention, the porosity of the oil-absorbing sponge can be selected in a wide range. According to a preferred embodiment of the present invention, the porosity of the oil-absorbing sponge is greater than or equal to 60%, preferably greater than or equal to 90%.

[0025] The oil-absorbing sponge of the present invention has super-hydrophobic and super-oleophilic properties. According to a preferred embodiment of the present invention, the static plane contact angle of the surface of the oil-absorbing sponge to water in air is greater than 135°; preferably greater than 145°.

[0026] The oil-absorbing sponge of the present invention has super-hydrophobic and super-oleophilic properties. According to a preferred embodiment of the present invention, the static contact angle of the surface of the oil-absorbing sponge to white oil is less than 30°; preferably 0-20°; more preferably 0°.

[0027] The oil-absorbing sponge of the present invention also has flame retardant properties; according to a preferred embodiment of the present invention, the UL94 vertical burning test grade of the oil-absorbing sponge is above V-2, preferably above V-1; more preferably V-0.

[0028] The oil-absorbing sponges having the above-mentioned characteristics of the present invention can achieve the purpose of the present invention, and there is no special requirement for the preparation method thereof. With respect to the present invention, according to a preferred embodiment of the present invention, the second aspect of the present invention provides a method for preparing the oil-absorbing sponge of the present invention, the method comprising:

[0029] The solution containing the thermosetting resin prepolymer and the curing agent is dispersed into the three-dimensional porous polymer matrix, and cured under vacuum conditions to obtain the oil-absorbing sponge. The preparation method of the present invention disperses (for example, by extrusion absorption dispersion, spray absorption dispersion) the solution containing the thermosetting resin prepolymer and the curing agent into the three-dimensional porous polymer matrix and then heats and cures it in vacuum, which can cure the thermosetting resin on the three-dimensional porous polymer matrix while maintaining the high resilience and high porosity of the original three-dimensional porous polymer matrix.

[0030] In the present invention, there is no particular limitation on the dispersion method of dispersing the solution containing thermosetting resin prepolymer and curing agent into the three-dimensional porous polymer matrix, as long as it can be evenly dispersed. According to a preferred embodiment of the present invention, the dispersion method is extrusion absorption dispersion or spray absorption dispersion, preferably extrusion absorption dispersion.

[0031] In the present invention, extrusion absorption dispersion refers to extruding the three-dimensional porous polymer matrix, placing it in a solution containing a thermosetting resin prepolymer and a curing agent, absorbing and restoring it to its original morphology, and then extruding it to a certain proportion to discharge the excess solution and disperse it evenly.

[0032] In the present invention, spray absorption dispersion refers to uniformly dispersing a certain amount of thermosetting resin prepolymer and curing agent solution onto the surface of the three-dimensional porous polymer matrix in a spraying manner, waiting for absorption and then heating and curing.

[0033] In the present invention, the curing pressure may be selected in a wide range. According to a preferred embodiment of the present invention, the pressure is 0 to 10 kPa, preferably 3 to 5 kPa.

[0034] In the present invention, the curing conditions have a wide range of optional ranges. According to a preferred embodiment of the present invention, the curing conditions include: a temperature of 80 to 200°C, preferably 100 to 180°C; the curing time can be reasonably adjusted according to actual needs, preferably, the time is 5 to 120 minutes, more preferably 20 to 100 minutes.

[0035] According to a preferred embodiment of the present invention, the method for preparing the oil-absorbing sponge comprises:

[0036] (1) dispersing a solution containing a thermosetting resin prepolymer and a curing agent into a three-dimensional porous polymer matrix, and pre-curing under a first vacuum condition;

[0037] (2) dispersing a solution containing a thermosetting resin prepolymer and a curing agent into the product obtained in step (1), and curing the product under a second vacuum condition;

[0038] The first vacuum condition and the second vacuum condition each include: a pressure of 0-10KPa;

[0039] Pre-curing conditions include: temperature of 80-120°C;

[0040] Curing conditions include: temperature of 140-180°C.

[0041] In the present invention, the thermosetting resin prepolymer is pre-cured to make the overall temperature of the sponge uniform, the thermosetting resin inside reaches a gel state, and is attached to the three-dimensional porous polymer matrix skeleton. The vacuum condition is conducive to the gas discharge in the thermosetting resin in the gel state, and better combined with the sponge skeleton. Then, the solution containing the thermosetting resin prepolymer and the curing agent is dispersed on the three-dimensional porous polymer matrix containing the gel-state thermosetting resin, and cured to obtain the oil-absorbing sponge, which is conducive to the uniform distribution of the thermosetting resin on the sponge skeleton, thereby maintaining the elasticity of the three-dimensional porous polymer matrix, improving the recyclable performance of the oil-absorbing sponge, and the adsorption capacity is basically not attenuated when it is recycled for 30 times.

[0042] According to a preferred embodiment of the present invention, in step (1), the gel-state thermosetting resin accounts for 0.5-1% of the total mass of the sponge, which is beneficial to further maintain the elasticity of the three-dimensional porous polymer matrix and improve the recycling performance of the oil-absorbing sponge.

[0043] In the present invention, in step (1), there is no special requirement for the pre-curing time, which can be reasonably adjusted according to actual needs, as long as the thermosetting resin prepolymer forms a gel-state thermosetting resin in the three-dimensional porous polymer matrix. According to a preferred embodiment of the present invention, the pre-curing time is 40-90 minutes.

[0044] In the present invention, in step (2), the curing time is 20-100 minutes.

[0045] According to a preferred embodiment of the present invention, in the solution containing the thermosetting resin prepolymer and the curing agent, the mass concentration of the thermosetting resin prepolymer is 0.02 to 0.6 g / mL, preferably 0.03 to 0.5 g / mL, and more preferably 0.05 to 0.3 g / mL.

[0046] According to a preferred embodiment of the present invention, in the solution containing the thermosetting resin prepolymer and the curing agent, the mass of the curing agent accounts for 1 to 10% of the mass of the thermosetting resin prepolymer; preferably 5 to 10%.

[0047] In the present invention, in the solution containing thermosetting resin prepolymer and curing agent, the optional range of solvent is relatively wide, as long as it can dissolve the thermosetting resin prepolymer and the curing agent. According to a preferred embodiment of the present invention, in the solution containing thermosetting resin prepolymer and curing agent, the solvent is selected from at least one of water, C1-C4 alcohol and C1-C4 ketone; preferably ethanol and / or acetone.

[0048] In the present invention, in the solution containing the thermosetting resin prepolymer and the curing agent, the curing agent has a wide range of options, as long as it can form the thermosetting resin with the thermosetting resin prepolymer. According to a preferred embodiment of the present invention, the curing agent is selected from at least one of organic acids, acid anhydrides, boron trifluoride, aliphatic polyamines and aromatic polyamines; preferably at least one of benzenesulfonic acid, hexamethylenetetramine and meta-phenylenediamine.

[0049] The third aspect of the present invention provides an application of the oil-absorbing sponge of the present invention in treating oily wastewater. The oil-absorbing sponge of the present invention is used for treating oily wastewater, has strong selectivity for oil products in oily wastewater, has a large adsorption capacity for oil products and can be recycled. The adsorption capacity does not decay after being recycled for 30 times. Compared with traditional activated carbon, oil-absorbing felt and other materials, the generation of waste solids is significantly reduced, and the use cost is also reduced.

[0050] The present invention will be described in detail below through examples.

[0051] In the following examples, the vertical burning test grade is tested according to the UL94 flame retardant test method.

[0052] In the following test examples, the saturated oil phase adsorption and the saturated oil phase adsorption after 30 cycles were tested using the following steps: weigh the mass of the sponge to be tested m1, place it in a beaker filled with 200mL toluene, weigh the mass of the sponge after adsorption saturation m2, and the saturated oil phase adsorption (Ф): Ф = m1 / m2. The test of the saturated oil phase adsorption after 30 cycles was first performed by saturating the sponge with toluene, mechanically squeezing it until no oil phase dripped naturally, and repeating it 30 times. The subsequent test steps were consistent with the saturated oil phase adsorption.

[0053] In the following embodiments, the water contact angle parameters were measured using the EASY DROP contact angle tester from KRUSS, Germany, with a measurement range of 1-180° and a resolution of ±0.1°. A static contact angle measurement mode was used, and a water droplet or white oil droplet with a fixed volume of 2 μL was dropped on the sponge each time. The calculated initial contact angle was taken as the contact angle measurement value of the sponge surface. Six parallel measurements were performed to calculate the average value.

[0054] In the following examples, the oil phase removal rate and oil phase selective adsorption rate of oily wastewater are measured by the following steps: 1000 mL of the same batch of oily wastewater (oil content 10%, oil phase components C7-C9), 10 g of the sample to be tested is weighed, and placed in the above oily wastewater for adsorption for 10 minutes. The volume V1 and oil phase content C1 of the remaining oily wastewater are tested. Oil phase removal rate (β): β = (1-C1V1 / 100) × 100%; oil phase selective adsorption rate (θ): θ = (100-C1V1) / (1000-V1).

[0055] In the following examples, the porous melamine-formaldehyde sponge matrix (Xuxian Industrial) had a porosity of 95% and an average pore size of 100 μm;

[0056] The porous melamine-formaldehyde sponge matrix (Beiyou Building Materials) has a porosity of 96% and an average pore size of 250 μm.

[0057] Example 1

[0058] (1) Weigh 10 g of phenolic resin prepolymer solution (plasticized by Meisheng Chemical) and 1 g of hexamethylenetetramine and dissolve them in 200 mL of ethanol. Stir thoroughly to make the solution clear and transparent.

[0059] (2) A 200*200*150 mm porous melamine-formaldehyde sponge matrix (Xuxian Industrial) was measured and the above solution was dispersed into the sponge by extrusion dispersion so that the curing agent solution evenly infiltrated the sponge. The extruded sponge was placed in a vacuum oven at 180°C and 3 kPa for curing for 20 min to obtain an oil-absorbing sponge S1.

[0060] In the oil-absorbing sponge S1, the mass of phenolic resin accounts for 2% of the total mass of the oil-absorbing sponge; the average pore size of the oil-absorbing sponge S1 is 100 μm, the porosity is 95%, the open porosity is 98%, the vertical combustion grade is V-0, the contact angle to white oil is 0°, the contact angle to water is 152.3°; the saturated oil phase adsorption amount is 40 g / g.

[0061] The sponge was tested for saturated oil phase adsorption, oil phase removal rate and oil phase selective adsorption rate after 30 cycles according to the test requirements. The results are shown in Table 1.

[0062] Among them, the SEM image of the oil absorbing sponge S1 is as follows Figure 1 As shown, compared with the melamine-formaldehyde sponge matrix (SEM image as Figure 3 ), the porous skeleton size of the oil-absorbing sponge is slightly larger than that before modification, indicating that the phenolic resin is uniformly solidified on the surface of the porous melamine-formaldehyde sponge matrix skeleton and has through holes, which makes the oil-absorbing sponge highly selective for oil products in oily wastewater and has a large adsorption capacity for oil products.

[0063] Figure 2 The SEM image of the oil-absorbing sponge S1 after 30 cycles. Figure 1 Compared with the above, there is basically no change, so the adsorption capacity of the oil-absorbing sponge has basically not declined when it is recycled 30 times.

[0064] Example 2

[0065] (1) Weigh 10 g of phenolic resin prepolymer solution (plasticized by Meisheng Chemical), 0.3 g of hexamethylenetetramine and 0.2 g of m-xylylenediamine and dissolve them in 200 mL of ethanol. Stir thoroughly to make the solution clear and transparent.

[0066] (2) Weigh a 200*200*150 mm porous melamine-formaldehyde sponge matrix (Xuxian Industrial), and disperse the above solution into the sponge by extrusion dispersion so that the curing agent solution evenly infiltrates the sponge. Place the sponge after extrusion in a 140° C. vacuum oven for curing for 100 min to obtain an oil-absorbing sponge S2.

[0067] In the oil-absorbing sponge S2, the mass of phenolic resin accounts for 3% of the total mass of the sponge; the average pore size of the oil-absorbing sponge S2 is 100 μm, the porosity is 95%, and the open porosity is 98%; the vertical combustion grade is V-1, the contact angle to white oil is 0°, and the contact angle to water is 153.2°; the saturated adsorption capacity is 38 g / g.

[0068] The sponge was tested for saturated oil phase adsorption, oil phase removal rate and oil phase selective adsorption rate after 30 cycles according to the test requirements. The results are shown in Table 1.

[0069] Example 3

[0070] (1) Weigh 10 g of epoxy resin prepolymer solution (Willigut) and 0.6 g of hexamethylenetetramine and dissolve them in 200 mL of acetone. Stir thoroughly to make the solution clear and transparent.

[0071] (2) Weigh a 200*200*150 mm porous melamine-formaldehyde sponge matrix (Beyou Building Materials), and disperse the above solution into the sponge by spraying so that the curing agent solution evenly infiltrates the sponge. Place the extruded sponge in a vacuum oven at 150°C and 5 kPa for curing for 20 min to obtain an oil-absorbing sponge S3.

[0072] In the oil-absorbing sponge S3, the mass of epoxy resin accounts for 3% of the total mass of the sponge; the average pore size of the oil-absorbing sponge S3 is 250 μm, the porosity is 96%, and the open porosity is 98%; the vertical combustion grade is V-0; the contact angle to white oil is 0°, and the contact angle to water is 151.1°; the saturated adsorption capacity is 40 g / g.

[0073] The sponge was tested for saturated oil phase adsorption, oil phase removal rate and oil phase selective adsorption rate after 30 cycles according to the test requirements. The results are shown in Table 1.

[0074] Example 4

[0075] The method of Preparation Example 3 was followed, except that the volume of the porous melamine-formaldehyde sponge matrix was 400*400*150 mm; the other conditions were the same as Preparation Example 3, to obtain oil-absorbing sponge S4.

[0076] In the oil-absorbing sponge S4, the mass of epoxy resin accounts for 0.5% of the total mass of the sponge; the average pore size of the oil-absorbing sponge S4 is 250 μm, the porosity is 92%, and the open porosity is 93%; the vertical combustion grade is V-0; the contact angle to white oil is 0°, and the contact angle to water is 146°; the saturated adsorption capacity is 37 g / g.

[0077] The sponge was tested for saturated oil phase adsorption, oil phase removal rate and oil phase selective adsorption rate after 30 cycles according to the test requirements. The results are shown in Table 1.

[0078] Example 5

[0079] The method of Preparation Example 3 was followed, except that 20 g of epoxy resin prepolymer solution (Willigut) and 1.2 g of hexamethylenetetramine were weighed and dissolved in 200 mL of acetone; the other conditions were the same as those of Preparation Example 3 to obtain oil-absorbing sponge S5.

[0080] In the oil-absorbing sponge S5, the mass of epoxy resin accounts for 5% of the total mass of the sponge; the average pore size of the oil-absorbing sponge S5 is 240 μm, the porosity is 87%, and the open porosity is 83%; the vertical combustion grade is V-1; the contact angle to white oil is 0°, and the contact angle to water is 155.4°; the saturated adsorption capacity is 32 g / g.

[0081] The sponge was tested for saturated oil phase adsorption, oil phase removal rate and oil phase selective adsorption rate after 30 cycles according to the test requirements. The results are shown in Table 1.

[0082] Example 6

[0083] (1) Weigh 10 g of phenolic resin prepolymer solution (plasticized by Meisheng Chemical) and 1 g of hexamethylenetetramine and dissolve them in 200 mL of ethanol. Stir thoroughly to make the solution clear and transparent.

[0084] (2) taking a 200*200*150 mm porous melamine-formaldehyde sponge matrix (Xuxian Industrial), dispersing the above solution into the sponge by extrusion dispersion, so that the curing agent solution evenly infiltrates the sponge, and curing the sponge after extrusion in a vacuum oven at 110° C. and 3 kPa for 80 min to obtain a sponge containing a gel-state phenolic resin; wherein the gel-state phenolic resin sponge accounts for 1% of the total mass of the porous melamine-formaldehyde sponge matrix;

[0085] (3) The solution of step (1) is dispersed into the sponge containing the gel-like phenolic resin obtained in step (2) by extrusion dispersion, so that the solution evenly infiltrates the sponge. The extruded sponge is placed in a vacuum oven at 180° C. and 3 kPa for curing for 20 min to obtain an oil-absorbing sponge S6.

[0086] The phenolic resin accounts for 2% of the total mass of the oil-absorbing sponge S6; the average pore size of the oil-absorbing sponge is 100 μm, the porosity is 95%, the open porosity is 98%, the vertical combustion grade is V-0, the contact angle to white oil is 0°, and the contact angle to water is 153.8°; the saturated oil phase adsorption amount is 44 g / g.

[0087] The sponge was tested for saturated oil phase adsorption, oil phase removal rate and oil phase selective adsorption rate after 30 cycles according to the test requirements. The results are shown in Table 1.

[0088] Example 7

[0089] (1) Weigh 10 g of phenolic resin prepolymer solution (plasticized by Meisheng Chemical) and 1 g of hexamethylenetetramine and dissolve them in 200 mL of ethanol. Stir thoroughly to make the solution clear and transparent.

[0090] (2) A 200*200*150 mm porous melamine-formaldehyde sponge matrix (Xuxian Industrial) was measured and the above solution was dispersed into the sponge by extrusion dispersion so that the curing agent solution evenly infiltrated the sponge. The sponge after extrusion was placed in a vacuum oven at 110° C. and 3 kPa for curing for 80 min to obtain a sponge containing gel phenolic resin; the pre-cured sponge was then placed in a vacuum oven at 180° C. and 3 kPa for curing for 20 min to obtain an oil-absorbing sponge S7.

[0091] In the oil-absorbing sponge S7, the mass of phenolic resin accounts for 2% of the total mass of the oil-absorbing sponge; the average pore size of the oil-absorbing sponge S8 is 100 μm, the porosity is 95%, the open porosity is 98%, the vertical combustion grade is V-0, the contact angle to white oil is 0°, the contact angle to water is 152.7°; the saturated oil phase adsorption amount is 41 g / g.

[0092] Comparative Example 1

[0093] The method of Preparation Example 1 was followed, except that the impregnation amount of the phenolic resin prepolymer was adjusted so that the mass of the phenolic resin accounted for 7% of the total mass of the oil-absorbing sponge. The remaining conditions were the same as those of Preparation Example 1, to obtain oil-absorbing sponge D1.

[0094] In the oil-absorbing sponge D1, the mass of phenolic resin accounts for 7% of the total mass of the sponge; the average pore size of the oil-absorbing sponge D1 is 230 μm, the porosity is 73%, and the open porosity is 69%; the vertical combustion grade is V-2; the contact angle to white oil is 0°, and the contact angle to water is 158.1°; the saturated adsorption capacity is 27 g / g.

[0095] Figure 4 is the SEM photo of sponge D1. Compared with oil-absorbing sponge S1 ( Figure 1 ), the skeleton and the joints of the sponge are obviously covered with more thermosetting resin, which reduces the porosity of the sponge and the corresponding saturated adsorption capacity. In addition, the distribution of thermosetting resin on the surface of the skeleton is uneven, which is prone to stress concentration during the cycle and causes the skeleton to collapse. Figure 5 This is a photo of the skeleton of sponge D1 after being recycled 30 times. The stacking density of the skeleton has increased significantly, resulting in a decrease in the saturated adsorption capacity.

[0096] The sponge was tested for saturated oil phase adsorption, oil phase removal rate and oil phase selective adsorption rate after 30 cycles according to the test requirements. The results are shown in Table 1.

[0097] Comparative Example 2

[0098] The method of Preparation Example 1 is followed, except that in step (2), curing is carried out under normal pressure, specifically: the sponge after extrusion is placed in an oven at 180° C. for curing for 20 minutes, and the other conditions are the same as those of Preparation Example 1, to obtain oil-absorbing sponge D2.

[0099] In the oil-absorbing sponge D2, the mass of phenolic resin accounts for 0.2% of the total mass of the sponge; the average pore size of the oil-absorbing sponge D2 is 250 μm, the porosity is 96%, and the open porosity is 98%; the vertical combustion grade is V-0; the contact angle to white oil is 0°, and the contact angle to water is 133.1°; the saturated adsorption capacity is 30 g / g.

[0100] The sponge was tested for saturated oil phase adsorption, oil phase removal rate and oil phase selective adsorption rate after 30 cycles according to the test requirements. The results are shown in Table 1.

[0101] Comparative Example 3

[0102] The unmodified melamine-formaldehyde sponge matrix was tested for saturated adsorption capacity, saturated oil phase adsorption capacity after 30 cycles, oil phase removal rate and oil phase selective adsorption rate according to the test requirements. The results are shown in Table 1.

[0103] Comparative Example 4

[0104] The oil-absorbing felt was tested for saturated adsorption capacity, saturated oil phase adsorption capacity after 30 cycles, oil phase removal rate and oil phase selective adsorption rate according to the test requirements. The results are shown in Table 1.

[0105] Table 1

[0106]

[0107] It can be seen from the results in Table 1 that the oil-absorbing sponge prepared by the present invention has high recycling capacity and oil-phase selective adsorption capacity, and can produce good effects in the treatment of oily wastewater.

[0108] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. An oil absorbing sponge, It is characterized in that The oil-absorbing sponge comprises a three-dimensional porous polymer matrix and a thermosetting resin coated on the three-dimensional porous polymer matrix; the saturated adsorption capacity of the oil-absorbing sponge for oil products is not less than 30 g / g; the saturated adsorption capacity of the oil-absorbing sponge for oil products is still not less than 30 g / g after 30 cycles of adsorption-desorption.

2. The oil-absorbing sponge according to claim 1, in, The mass of the thermosetting resin accounts for 0.5-5% of the total mass of the sponge; preferably 2-3%; and / or The saturated adsorption capacity of the oil-absorbing sponge for oil products is 30-50 g / g; the saturated adsorption capacity of the oil-absorbing sponge for oil products is still 30-50 g / g after being used in a desorption-adsorption cycle for 30 times.

3. The oil-absorbing sponge according to claim 1 or 2, in, The thermosetting resin is selected from at least one of phenolic resin, epoxy resin, urea-formaldehyde resin, unsaturated polyester resin and silicone resin; preferably selected from at least one of phenolic resin, epoxy resin and silicone resin; and / or The three-dimensional porous polymer matrix is ​​selected from at least one of melamine-formaldehyde sponge, polyurethane sponge and ethylene-vinyl acetate sponge, preferably melamine-formaldehyde sponge.

4. The oil-absorbing sponge according to any one of claims 1 to 3, in, The pore size of the oil absorbing sponge is 10-500 μm, preferably 100-400 μm; and / or The porosity of the oil-absorbing sponge is greater than or equal to 60%, preferably greater than or equal to 90%.

5. The oil-absorbing sponge according to any one of claims 1 to 4, in, The static plane contact angle of the surface of the oil-absorbing sponge to water in air is greater than 135°; and / or The static contact angle of the oil-absorbing sponge surface to white oil is less than 30°; and / or The UL94 vertical burning test grade of the oil absorbing sponge is above V-2.

6. A method for preparing the oil-absorbing sponge according to any one of claims 1 to 5, It is characterized in that The method includes: The solution containing thermosetting resin prepolymer and curing agent is dispersed into a three-dimensional porous polymer matrix, and cured under vacuum conditions to obtain the oil-absorbing sponge; the vacuum pressure is 0 to 10 kPa, preferably 3 to 5 kPa.

7. The preparation method according to claim 6, in, The dispersion method is extrusion absorption dispersion or spray absorption dispersion; and / or The vacuum pressure is 3-5 kPa; and / or The curing conditions include: a temperature of 80 to 200° C., preferably 100 to 180° C.; and a time of 5 to 120 min, preferably 20 to 100 min.

8. The preparation method according to claim 6 or 7, in, The preparation method of the oil absorbing sponge comprises: (1) dispersing a solution containing a thermosetting resin prepolymer and a curing agent into a three-dimensional porous polymer matrix, and pre-curing under a first vacuum condition; (2) dispersing a solution containing a thermosetting resin prepolymer and a curing agent into the product obtained in step (1), and curing the product under a second vacuum condition; The first vacuum condition and the second vacuum condition each include: a pressure of 0-10KPa; Pre-curing conditions include: temperature of 80-120°C; Curing conditions include: temperature of 140-180°C.

9. The preparation method according to claim 8, in, In step (1), the pre-cured resin accounts for 0.5-1% of the total mass of the sponge.

10. The preparation method according to claim 6 or 7, in, In the solution containing the thermosetting resin prepolymer and the curing agent, the mass concentration of the thermosetting resin prepolymer is 0.02 to 0.6 g / mL; and / or In the solution containing the thermosetting resin prepolymer and the curing agent, the mass of the curing agent accounts for 1-10% of the mass of the thermosetting resin prepolymer.

11. The preparation method according to any one of claims 6 to 10, in, The solvent in the solution containing the thermosetting resin prepolymer and the curing agent is selected from at least one of water, C1-C4 alcohol and C1-C4 ketone; and / or The curing agent is at least one selected from the group consisting of organic acids, acid anhydrides, boron trifluoride, aliphatic polyamines and aromatic polyamines.

12. Use of the oil-absorbing sponge according to any one of claims 1 to 5 in treating oily wastewater.

Citation Information

Patent Citations

  • High-strength and wear-resistant superhydrophobic composite material and preparation method thereof

    CN108659257A

  • Preparation method of flame-retardant superhydrophobic sponge with photothermal effect and magnetic driving function

    CN110003519A

  • Preparation method of hydrophobic oleophylic polyurethane sponge and oil-water separation device

    CN114805921A

  • Adiabatic panel with injecting heat-hardening resin into cavity of polystylene foam

    KR100542050B1

  • A method of installing a hood for kitchen

    KR102220571B1